2003
DOI: 10.1542/peds.112.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Health Insurance Status and Emergency Department Utilization in the United States

Abstract: Health insurance status was not associated with children's overall ED use or children's ED use for nonurgent problems at the national level. Our findings suggest that policy efforts in an attempt to relieve ED overcrowding conditions should look for measures beyond solely making changes in health insurance coverage for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 21 publications
4
47
3
1
Order By: Relevance
“…The insured had slightly more follow up clinic visits, more unscheduled clinic visits and twice more emergency room visits compared to their counterpart, the uninsured. This findings were similar to that of [16] Tanimola et al who reported 144% increase in the utilization of health service at university of Ilorin teaching hospital staff clinic and that of [8] reported increased likelihood of insured children visiting emergency room more than the uninsured children. The preponderance of emergency room visits among the insured may be due to absence of the deleterious effect of user fees on affordability of health services and drugs [5].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The insured had slightly more follow up clinic visits, more unscheduled clinic visits and twice more emergency room visits compared to their counterpart, the uninsured. This findings were similar to that of [16] Tanimola et al who reported 144% increase in the utilization of health service at university of Ilorin teaching hospital staff clinic and that of [8] reported increased likelihood of insured children visiting emergency room more than the uninsured children. The preponderance of emergency room visits among the insured may be due to absence of the deleterious effect of user fees on affordability of health services and drugs [5].…”
Section: Discussionsupporting
confidence: 90%
“…In general, it was reported in the available literature that health insurance coverage is associated with increase health resources utilization [8]. In this study, health services utilization of insured children with SCD was found to be significantly higher than those children without health insurance cover.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…30 Despite the much higher cost of ED visits, poor children are three times as likely as other children to use EDs for nonurgent care. 31 EDs, however, are neither intended nor prepared to deliver the preventive care that these children lack. Thus, while EDs provide an important safety net for vulnerable populations, they do so inefficiently.…”
Section: Voltage Drop 3: Access To Covered Services and Providersmentioning
confidence: 99%
“…Os serviços de urgência do Sistema Único de Saúde (SUS) destinados às crianças gravemente enfermas são também freqüentados por crianças com doenças mais simples, e as famílias os utilizam como porta de entrada ao sistema 4,9,10 , provocando elevada procura pelos serviços e interferindo no atendimento aos pacientes agudos, que são obrigados a enfrentarem as filas, embora cada serviço apresente um sistema de priorização mais ou menos eficiente.…”
Section: Introductionunclassified